Pengaruh Keluarga Dalam Manajemen Pendidikan Moderasi Beragama - Supiah; Podungge, Mariaty (Lembaga Penelitian dan Pengabdian Kepada Masyarakat of Institut Agama Islam Negeri Metro, 2024)
Religious moderation, defined as a balanced approach in practicing religion by avoiding extremism in the form of radicalism or liberalism, is crucial for maintaining social harmony in diverse societies. The family, as the first educational institution, holds a strategic role in instilling the values of religious moderation in children from an early age. This study aims to examine the influence of the family's role in managing religious moderation education for children in West Sipatana. A quantitative method with a simple regression analysis approach was employed to measure the extent of the family's impact on religious moderation education. Field findings reveal that the family contributes 75% to shaping children's attitudes toward religious moderation. These findings indicate that active family involvement in children's religious education, such as teaching respect for differing beliefs and fostering constructive dialogue, significantly influences the development of tolerant and inclusive moderate attitudes in children. This research underscores the vital role of families as primary actors in supporting religious moderation education in society.